THE EFFECT OF BANANAS (MUSA PARADISIACA) ON REDUCING BLOOD PRESSURE IN PREGNANT WOMEN - Lisna Nurfitriana; Siti Mardhatillah Musa (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Hypertension in pregnancy is one of the leading causes of maternal and fetal morbidity and mortality worldwide. This study aims to analyze the effect of banana (Musa paradisiaca) consumption on reducing blood pressure in pregnant women with hypertension. The research method used was a literature review of 20 research articles consisting of quasi-experimental, pre-experimental, and case study designs. The population in this study were pregnant women with hypertension, while the sample consisted of 20 research results that met the inclusion criteria. Instruments used in these studies included a sphygmomanometer and a blood pressure observation sheet. Data analysis was conducted using narrative synthesis of relevant research results. The results showed that most studies reported a significant decrease in systolic and diastolic blood pressure after consuming bananas at a dose of 100–200 grams per day for 5–14 days, with a p value <0.05. Ambon bananas are the most frequently used type and have shown consistent effectiveness as a complementary therapy. The conclusion of this study is that banana consumption has an effect on lowering blood pressure in pregnant women with hypertension and can be used as a complementary non-pharmacological therapy, although there are still limitations in sample size and research design.